Reading comprehension level of grade 10 students : basis for a multimedia intervention material - Espino, Sheri Nadia E. (Pangasinan : [s.n.], 2017)
This study aimed to develop and evaluate a Multimedia Intervention Material in Reading Comprehension for grade 10 students. It determined the reading comprehension level of grade 10 students as to the three dimensions: literal comprehension, inferential comprehension and evaluative comprehension. There were 355 grade 10 students among six public secondary schools of the third congressional district of Pangasinan, namely: Bayambang National High School, Calasiao Comprehensive National High School, Daniel Maramba National High School, Malasiqui National High School, Mapandan National High School and Speaker Eugenio Perez National Agricultural School in San Carlos City.
Bibliography: pages 156-160.
CHED-La Union
Keywords: Reading comprehension